2016
DOI: 10.1186/s40064-016-3601-7
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive treatment of tibial pilon fractures through arthroscopy and external fixator-assisted reduction

Abstract: ObjectiveThe aim of this study was to evaluate the clinical outcome of tibial pilon fractures treated with arthroscopy and assisted reduction with an external fixator.MethodsThirteen patients with tibial pilon fractures underwent assisted reduction for limited lower internal fixation with an external fixator under arthroscopic guidance. The weight-bearing time was decided on the basis of repeat radiography of the tibia 3 months after surgery. Postoperative ankle function was evaluated according to the Mazur sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
(19 reference statements)
0
15
0
2
Order By: Relevance
“…All surgeries were performed by experienced surgeons. EFLIF has been commonly used in clinical practice and previously described by Marin et al 12 As described by Luo et al, arthroscopy-assisted minimally invasive therapy was performed in the following steps: 13 1) broken end was exposed through one posterolateral fibular incision, and plate fixation was performed after reduction under direct vision; 2) external fixator was used to achieve indirect reduction, protect soft tissue and reconstruct limb length; 3) two sides of distal tibia were unfolded to obtain adequate space in the ankle joint available for arthroscopy; 4) arthroscopic camera and instrument (Stryker Corporation, Kalamazoo, MI, USA) were inserted into the ankle through two incisions at the front of the ankle for observation and reduction, and blood clots and bone scraps were cleared under arthroscopy. One longitudinal tibial incision was made near the joint surface, and broken bone was exposed after blunt dissection.…”
Section: Methodsmentioning
confidence: 99%
“…All surgeries were performed by experienced surgeons. EFLIF has been commonly used in clinical practice and previously described by Marin et al 12 As described by Luo et al, arthroscopy-assisted minimally invasive therapy was performed in the following steps: 13 1) broken end was exposed through one posterolateral fibular incision, and plate fixation was performed after reduction under direct vision; 2) external fixator was used to achieve indirect reduction, protect soft tissue and reconstruct limb length; 3) two sides of distal tibia were unfolded to obtain adequate space in the ankle joint available for arthroscopy; 4) arthroscopic camera and instrument (Stryker Corporation, Kalamazoo, MI, USA) were inserted into the ankle through two incisions at the front of the ankle for observation and reduction, and blood clots and bone scraps were cleared under arthroscopy. One longitudinal tibial incision was made near the joint surface, and broken bone was exposed after blunt dissection.…”
Section: Methodsmentioning
confidence: 99%
“…Review of current literature identified 2 studies, 1 nonblinded randomized controlled trial (RCT) and 1 case series, that met criteria for this review. 25,26 The total number of patients from these studies was 243. There were 166 men and 77 women with ages ranging from 19 to 68 years old.…”
Section: Pilon Fracturesmentioning
confidence: 99%
“…Ankle arthroscopy is a therapeutic procedure for ankle osteoarthritis, chondral lesion, loose body, and soft tissue impingement. [1][2][3][4][5] It is also performed as a diagnostic procedure for intra-articular disease. 6 For arthroscopic ankle surgery, possible anesthetic methods include spinal anesthesia (SA), nerve block, and local anesthesia (LA).…”
Section: Introductionmentioning
confidence: 99%